Analysis of Safety Street Food In Public Primary Schools in Padang City - Fajri, Prima Yaumil; Refdi, Cesar Welya; Fiana, Risa Meutia (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
Food safety is the main issue in street food for student in primary school. Street food that unhealthy can be caused by unhygienic food processing or storage. Microbial contamination, chemical contamination from the air or application of food additives at risk become critical point food safety in street food for student in primary school. The aim of this research was to know street food that often consumed by students some public primary schools in Padang City and its safety. This research is an observational study with purposive sampling technique. The result of this research showed that there is chemical contamination from lead, may caused of the location of food stall and how it is processed. Street food of school children observed from selected public primary schools in Padang City was suspected of containing borax and formalin proved negative.Keywords : borax, chemical contamination, formalin, lead, street food